Valid and Reliable Attitude Scales for Measuring Clinician’s Attitudes Towards Telehealth Assisted Sexual Assault Forensic Exams Using a Pre-Post Survey - Wah Wah Myint DrPH; Heather R. Clark DrPH; Kim Zemanek PhD; Kayce Ward MSN; Stacey A. Mitchell DNP; Nancy R. Downing PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The success of telehealth programs to guide clinicians to perform sexual assault medical forensic examinations relies on clinicians’ positive attitudes toward telehealth services, though no validated tools to measure these variables exist. This study aims to report validity and reliability of a novel tool with two scales: Positive Beliefs and Acceptance scales for hospital nurse clinicians at sites initiating the Texas Teleforensic Remote Assistance Center (Tex-TRAC). An analysis of pre-post cross-sectional data of hospital nurse clinicians (N = 121) trained in the use of Tex-TRAC telehealth technology at seven participating hospitals in Texas from July 2022 to May 2023 was performed. The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy and Bartlett’s test of Sphericity sample size analysis were performed. Exploratory Factor Analysis (EFA) was applied for validity and internal consistency reliability Cronbach alpha (α) values were described for two scales: Positive Beliefs and Acceptance scales. Positive Beliefs scale has a KMO value of 0.810 and Barlett’s test of sphericity (χ 2 (6) = 380.47, P  < .001). Acceptance scale has a KMO value of 0.832 and Barlett’s test of sphericity (χ 2 (28) = 432.19, P  < .001). After Promax Oblique rotation, the final four-item Positive Beliefs scale had α = .894; the final five-item Acceptance scale had α = .876. Validity and reliability of both scales demonstrated potential usefulness for future telehealth interventions engaging Sexual Assault Nurse Examiners. Continued use of these scales could provide additional information that can be leveraged in training curriculum of similar telehealth programs like Tex-TRAC.